2017
DOI: 10.1039/c7ra09002a
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent carbon dots derived from sugarcane molasses: synthesis, properties, and applications

Abstract: Photoluminescent carbon dots derived from sugarcane molasses were investigated via cellular imaging and sensing for Fe3+ or sunset yellow. The underlying mechanism of fluorescence quenching in the C-dots/sunset yellow system was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 41 publications
0
53
2
Order By: Relevance
“…In the spectrum, lower cutoff wavelengths for the CQDs were observed at 235 and 332 nm. Absorption of the CQDs was attributed to the π–π * transition of aromatic C=C bonds and the n–π * transition of surface functional groups such as C=O . A broad peak at 332 nm in the visible absorption spectrum of the CQDs appeared due to trapping of large amounts of excitation energy, leading to huge amounts of emission at 365 nm excitation and indicated that the prepared CQDs were fluorescent .…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum, lower cutoff wavelengths for the CQDs were observed at 235 and 332 nm. Absorption of the CQDs was attributed to the π–π * transition of aromatic C=C bonds and the n–π * transition of surface functional groups such as C=O . A broad peak at 332 nm in the visible absorption spectrum of the CQDs appeared due to trapping of large amounts of excitation energy, leading to huge amounts of emission at 365 nm excitation and indicated that the prepared CQDs were fluorescent .…”
Section: Resultsmentioning
confidence: 99%
“…CDots are small carbon nanoparticles of an average diameter of ,10 nm that are functionalized with organic molecules such as those containing amino groups for effective surface passivation. 5 Due to their biocompatibility and low toxicity in vitro and in vivo, CDots have been widely pursued for a broad range of promising biological applications, including biosensors, gene transmission, drug delivery, and fluorescence labeling. 6 It is known that the optical absorption of CDots is associated with π-plasmon transitions in the core carbon nanoparticles of the dots, while the fluorescence emissions over the visible to near-infrared spectral region are attributed to photogenerated electrons and holes trapped at diverse surface sites and their associated radiative recombinations.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors showed promising biocompatibility properties of fluorescent CDs conjugated with hyperbranched polyglycerol, which had improved performances in terms of RBCs morphology and hemolysis respect to bare unmodified CDs [117]. Minimum RBC toxicity and negligible hemolytic effect were confirmed by different experimental in vitro studies with CDs at concentration up to 2.0 mg/mL [118,119], while only slight effects were observed on the α-helix structure of BSA following incubation with CDs derived from sugarcane molasses [119]. An in vivo toxicology testing showed normal values for the hematology parameters, including white blood cells, red blood cells, hemoglobin concentration, and platelet count following CDs injection in female Balb/c mice over 90 days [17].…”
Section: Carbon Dotsmentioning
confidence: 84%